EXISTENCIA DE UNA MEDIDA INVARIANTE EN ALGUNAS ECUACIONES DE EVOLUCIÓN ESTOCÁSTICAS - Balcázar Huapaya, Claudio Fernando (2006)
We study the stochastic process shaped with the solution of a stochastic evolution equation. We prove the theorem of the existence of a invariant measure in the Banach space of the values of the random variables, satisfying suitables hypothesis in the mentioned stochastic process. The initial-boundary value problem for the von Karman plate with random term of Brownian motion is a model where to build a invariant measure.